Mineral resources in the world and Russian economics. Part 1. Mineral complex of the world and Russia - E. A. Kozlovsky (Известия высших учебных заведений: Геология и разведка, 2015)
On the basis of analisis of different countries economical indexes their economy is shown to be linked tightly with the mineral resources and possibilites of the countries to build their own independent policy. Russia is concluded to have lack of thought and scientifically proven state strategy of development and use of mineral resources, based on the model of self-maintenance with required degree of export and limited import. Such situation puts the national safety of the country under threat and leads to the lost of geopolitical priorities in the world mineral sector. The number of measures of the principal break in the state policy in the sphere of geological studing of the subsurface, reproductation of the mineral base, management of the geological investigations. While development of the new concept of the low «about subsurface» it’s needed to take into account the main thing - economical safety of the country.